2016
DOI: 10.18632/oncotarget.12909
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog pathway dysregulation contributes to the pathogenesis of human gastrointestinal stromal tumors via GLI-mediated activation of KIT expression

Abstract: Gastrointestinal stromal tumors (GIST) arise within the interstitial cell of Cajal (ICC) lineage due to activating KIT/PDGFRA mutations. Both ICC and GIST possess primary cilia (PC), which coordinate PDGFRA and Hedgehog signaling, regulators of gastrointestinal mesenchymal development. Therefore, we hypothesized that Hedgehog signaling may be altered in human GIST and controls KIT expression. Quantitative RT-PCR, microarrays, and next generation sequencing were used to describe Hedgehog/PC-related genes in pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 50 publications
4
35
0
2
Order By: Relevance
“…27 It is reported that PTCH1 gene mutation is associated with gastrointestinal stromal-like tumors in mice 28 and contributes to the pathogenesis of human gastrointestinal stromal tumors via GLI-mediated activation of KIT expression. 29 To the best of our knowledge, PTCH1 gene mutation is not recorded in pediatric GIST, therefore, we know little in pediatric populations and no corresponding medicine exists for GIST treatment.…”
Section: Discussionmentioning
confidence: 99%
“…27 It is reported that PTCH1 gene mutation is associated with gastrointestinal stromal-like tumors in mice 28 and contributes to the pathogenesis of human gastrointestinal stromal tumors via GLI-mediated activation of KIT expression. 29 To the best of our knowledge, PTCH1 gene mutation is not recorded in pediatric GIST, therefore, we know little in pediatric populations and no corresponding medicine exists for GIST treatment.…”
Section: Discussionmentioning
confidence: 99%
“…В работе C.-M. Tang и соавт. [21] установлена вариабельная экспрессия некоторых HH-ассоциированных генов в изолированных интерстициальных клетках Кахаля и клетках ГИСО чело-века и грызунов независимо от мутационного статуса. Кроме того, авторы зафиксировали потенциально значи-мые геномные альтерации в ключевых генах HH-пути (PTCH1, PTCH2, SMO, SUFU, GLI1) в 10% исследуемых образцов ГИСО.…”
Section: Clinical and Morphological Characteristics Of Gastrointestinunclassified
“…При этом фармакологическая или гене-тическая блокада определенных звеньев сигналинга (на-пример, GLI1/2) приводила к снижению экспрессии KIT и жизнеспособности опухолевых клеток, в том числе ре-зистентных к иматинибу. По мнению авторов, получен-ные результаты свидетельствуют, что HH-путь является перспективной фармакологической мишенью для лече-ния ГИСО [21].…”
Section: Clinical and Morphological Characteristics Of Gastrointestinunclassified
“…Sonic Hedgehog (Shh), as a member of the Hedgehog family, is usually activated in several types of tumors [ 1 ]. Shh proteins can bind to the transmembrane receptor Patched (Ptch) and enhance the activity of transmembrane protein Smoothened (SMO), then lead to activated transcription of GLI1, GLI2, and GLI3 , which are 3 transcription factor genes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%